Ectopic pregnancy, its potential links to dementia risk and interactions with depression: insights from a nationwide cohort study - Yao, Chia-Yi; Chung, Chi-Hsiang; Chien, Wu-Chien; Li, Sung-Tao; Lee, Siou-Ting; Huang, Chih-Chung; Yang, Chuan-Chi; Tzeng, Nian-Sheng (Frontiers in Psychiatry, 2024)
Background Dementia poses a growing global mental health impact, with variations in prevalence by gender, possibly influenced by reproductive factors. Ectopic pregnancy (EP), known for its association with cardiovascular diseases and depression, which are also predictors of dementia, prompted an exploration of their interplay. Methods Using Taiwan’s National Health Insurance Research Database, this nationwide cohort study examined 53,096 individuals to investigate the link between EP and dementia. Covariates included age, insured premiums, comorbidity by Charlson Comorbidity Index revised by excluding dementia, level of care, and residence. Surgical approaches, number of EP episodes, and dementia subtypes were considered in outcomes analysis using Cox regression. Results Among 13,274 women diagnosed with EP, 791 developed dementia over a 15-year follow-up, particularly vascular dementia. Adjusting for the covariates, the adjusted sub-distribution Hazard Ratio (asHR) with competing risks was 1.644 (95% CI, 1.394–2.053; p < 0.001). For patients with more than one episode, it was even higher (asHR=1.670 [95% CI, 1.419–2.092; p < 0.001]). Post-ectopic depression, prevalent in 62.2% within four weeks, was associated with a greater dementia risk compared to those without (asHR=1.702 [95% CI, 1.444-2.125; p<0.001] vs. asHR=1.551 [95%CI, 1.310-1.937; p<0.001]). Antidepressant treatments showed a partial protective effect, reducing the increased risk by 14.7%. Conclusion An EP history is linked to an earlier onset and a higher risk of overall dementia, VaD in particular, in a dose dependent manner, regardless of surgical intervention and stroke. Post-ectopic depression exacerbates dementia risk, while antidepressants offer partial protection. These findings underscore the potential benefit of screening and treating depression in women following EPs.